Should Achievement Tests be Used to Judge School Quality? - Bauer, Scott C. (Education Policy Analysis Archives, 2000)
This study provides empirical evidence to answer the question whether student scores on standardized achievement tests represent reasonable measures of instructional quality. Using a research protocol designed by Popham and the local study directors, individual test items from a nationally-marketed standardized achievement test were rated by educators and parents to determine the degree to which raters felt that the items reflect important content that is actually taught in schools, and the degree to which raters felt that students' answers to the questions would be likely to be unduly influenced by confounded causality. Three research questions are addressed: What percentage of test items are considered suspect by raters as indicators of school instructional quality? Do educators and parents of school-age children differ in their ratings of the appropriateness of test items? Do educators and parents feel that standardized achievement test scores should be used as an indicator of school instructional quality? Descriptive statistics show that on average, raters felt that the content reflected in test questions measured material that is important for students to know. However, for reading and language arts questions, between about 20% to 40% of the items were viewed as suspect in terms of the other criteria.